INOVASI PELAKSANAAN PELAYANAN PUBLIK PADA KEPENGURUSAN PASPOR DI KANTOR IMIGRASI KELAS I KOTA PEKANBARU TAHUN 2022 - ', Ovaliando; ', Wazni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Public service providers are always required to innovate continuously according to needs and make it easier for the public to obtain public services. This research aims to determine innovations in implementing passport management at the Class 1 Immigration Office in Pekanbaru City. Using qualitative descriptive research methods to collect data using interview observation and documentation methods. Based on the research results, it shows that the passport processing innovation at the Pekanbaru City Class 1 Immigration Office has been able to fulfill the 4 components of innovation theory proposed by Roger, namely relative advantage, suitability, complexity and easy to observe. Passport processing innovation is in accordance with Law Number 6 of 2011 concerning Immigration and legal regulations. The innovations issued by the Pekanbaru City Class 1 Immigration Office are Pekanbaru Dusk Immigration serving Tuesday and Thursday (IKAN SELAIS), Thumb Human Rights, Immigration Serving On-Site (IKAN SEPAT) and passport services on Saturday and Sunday. Through this innovation, the public finds it easy to obtain excellent service provided by the Pekanbaru City Class 1 Immigration Office. Keywords: Innovation, Public Services, Passport Management